Neuroprotective effect of ebselen against intracerebroventricular streptozotocin-induced neuronal apoptosis and oxidative stress in rats - YANARTAŞ, ÖMER (SAGE PUBLICATIONS INC, 2016)
The goal of this study was to examine the neuroprotective effect of ebselen against intracerebroventricular streptozotocin (ICV-STZ)-induced oxidative stress and neuronal apoptosis in rat brain. A total of 30 adult male Sprague-Dawley rats were randomly divided into 3 groups of 10 animals each: control, ICV-STZ, and ICV-STZ treated with ebselen. The ICV-STZ group rats were injected bilaterally with ICV-STZ (3 mg/kg) on days 1 and 3, and ebselen (10 mg/kg/day) was administered for 14 days starting from 1st day of ICV-STZ injection to day 14. Rats were killed at the end of the study and brain tissues were removed for biochemical and histopathological investigation. Our results demonstrated, for the first time, the neuroprotective effect of ebselen on Alzheimer's disease (AD) model in rats. Our present study, in ICV-STZ group, showed significant increase in tissue malondialdehyde levels and significant decrease in enzymatic antioxidants superoxide dismutase and glutathione peroxidase in the frontal cortex tissue. The histopathological studies in the brain of rats also supported that ebselen markedly reduced the ICV-STZ-induced histopathological changes and well preserved the normal histological architecture of the frontal cortex tissue. The number of apoptotic neurons was increased in frontal cortex tissue after ICV-STZ administration. Treatment of ebselen markedly reduced the number of degenerating apoptotic neurons. The study demonstrates the effectiveness of ebselen, as a powerful antioxidant, in preventing the oxidative damage and morphological changes caused by ICV-STZ in rats. Thus, ebselen may have a therapeutic value for the treatment of AD.
Keywords: Intracerebroventricular streptozotocin; ebselen; oxidative stress; neuronal damage; neuronal apoptosis; rats; MILD COGNITIVE IMPAIRMENT; FREE-RADICAL THEORY; ALZHEIMERS-DISEASE; GLUTATHIONE-PEROXIDASE; CEREBRAL-ISCHEMIA; NEURODEGENERATIVE DISEASES; BRAIN CORTEX; ADULT RATS; ANTIOXIDANT; METABOLISM